This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Recall the alternating series test for convergence :
If a n decreases monotonically and n → ∞ lim a n = 0 , then n = k ∑ ∞ ( − 1 ) n a n converges.
1 1 − 2 1 + 3 1 − 4 1 + ⋯ = n = 1 ∑ ∞ n ( − 1 ) n + 1
Let a n = n 1 .
Condition 1: a n > a n + 1
n ⟹ n ⟹ n 1 < n + 1 < n + 1 > n + 1 1 ∀ n ≥ 0 ∀ n ≥ 1
Condition 2: n → ∞ lim a n = 0
n → ∞ lim n 1 = n → ∞ lim ∞ 1 = 0
Since both conditions are satisfied, n = 1 ∑ ∞ n ( − 1 ) n + 1 converges by the alternating series test.